Pemberdayaan Kelompok Tani Kelurahan Kedurus Melalui Sosialisasi Hidroponik - Alvina Dewi Hafzari; Muhammad Hanif Abdillah Amin; Muhammad Rizaldi Ega Pratama; Kinanti Resmi Hayati (LPPM Universitas Dharma Andalas, 2022)
Empowerment is a concept where a change effort is made to provide strength and increase the ability of a group to have more value. Empowerment carried out among the community aims to improve the ability of the community in various ways so that they can meet their life needs, as well as improve their own welfare. KKNT Group 04 students in carrying out KKN activities found a problem in farmer groups in Kedurus Village, where these problems were closely related to community empowerment. The problems that occur are in terms of nursery management and marketing management. Therefore, KKNT Group 04 students provided a solution in the form of holding a hydroponic outreach activity with the theme 'Creating Innovative and Social Enterprise-Based Hydroponic Plant Development. problems they face, so that their crop yields can increase, and the income they earn increases.